Metal-organic framework nanosheets: An emerging family of multifunctional 2D materials - Duan, Jingui; Li, Yanshuo; Pan, Yichang; Behera, Nibedita; Jin, Wanqin (Coordination chemistry reviews, 2019)
[Display omitted] •Representative studies were given with emphasis on methods for preparation of metal organic framework nanosheets.•Crucial technologies for characterization of metal organic framework nanosheets were evaluated.•Series of promising applications by metal organic framework nanosheets were surveyed and discussed. With infinite assembly and ultrathin nature, metal-organic frameworks nanosheets (MOFNs), as an emerging family of two-dimensional (2D) materials, have attracted extensive interest in fields of material science, chemistry and nanotechnology. Here, we aim to review the recent advances of MOFNs. The assortments of their synthetic methods of top-down, bottom-up and combined strategies are discussed at first, including the comparison of their advantages and limitations. Then, some crucial techniques towards the morphology and microstructure characterization of MOFNs were introduced. We have also discussed the wide ranges of potential applications, especially molecular separation, catalyst, energy conversion, conduction, photofunction, electrochromism and sensing. Finally, the challenges and outlooks for these multi-functional 2D materials were prospected based on current achievements, as well as their unique architectural features.